Urban-rural communities attitudes and perceptions toward wildlife meat consumption in Bintulu, Sarawak - Thomas, Alexander; Mariapan, Manohar; Lim, Evelyn Ai Lin; Johari, Shazali (Malaysian Forester, 2023)
There are many types of forests in Sarawak that support various species of wildlife. In Sarawak, consuming wildlife meat is common among local communities especially those residing in rural areas where they hunt wildlife for their own consumption. Logging activities and the construction of roads have increased accessibility into the forests, and the connection between rural and urban areas. This has created the potential for wildlife meat commercial trade. However, the behaviour of local communities pertaining to wildlife meat consumption is understudied in Malaysia. This study aims to determine local communities attitudes and perceptions toward consuming wildlife meat and their wildlife meat preferences in Bintulu. Local communities attitudes and perceptions toward wildlife meat consumption were compared between the urban-rural communities. The findings showed that the local communities in Bintulu have a neutral attitude and perception toward consuming wildlife meat. The neutral tendency is attributed to their mixed responses toward consuming wildlife meat. Although the local communities do not depend on wildlife meat as their source of food, they consume it as part of their social and cultural beliefs and tradition. They also have the tendency of choosing neutral responses to state their attitudes and perceptions towards wildlife meat consumption statements. Despite their neutral attitude and perception, rural communities have a tendency to consume wildlife meat compared to urban communities. Among the wildlife meat, wild boar meat is the most preferred. The findings provide guidance towards developing successful strategies and actions to influence local communities towards sustainable use of wildlife for consumption.